Diagnosing and following adult patients with acute myeloid leukaemia in the genomic age. (7th August 2014) - Roug, Anne S.; Hansen, Marcus C.; Nederby, Line; Hokland, Peter
Summary The diagnosis and follow‐up process of adult patients with acute myeloid leukaemia (AML) is challenging to clinicians and laboratory staff alike. While several sets of recommendations have been published over the years, the development of high throughput screening and characterization for both genetic and epigenetic events have evolved with astonishing speed. Here we attempt to provide a practical guide to diagnose and follow adult AML patients with a focus on how to balance the wealth of information on the one hand, with the restriction put on these processes in terms of time, feasibility and economy when caring for these patients, on the other.